Electrical stimulation inhibits cytosine arabinoside-induced neuronal death by preventing apoptosis in dorsal root ganglion neurons - Han, Sungmin; Kim, Donghwee; Kim, Hyungmin; Park, Jong Woong; Youn, Inchan (LIPPINCOTT WILLIAMS & WILKINS, 2016)
The current study aimed to investigate whether electrical stimulation could prevent apoptotic neuronal cell death during treatment with cytosine arabinoside (ara-C). From in-vitro experiments, the effects of electrical stimulation were assessed on neurite fragmentation and neuronal cell death in ara-C-treated dorsal root ganglion (DRG) explants. Ara-C treatment increased neurite fragmentation and neuronal cell death in DRG explants and activated caspase-3 by cleaving it, which could induce apoptosis. Electrical stimulation can significantly reduce neurite fragmentation and neuronal cell death compared with nonelectrically stimulated groups. Furthermore, electrical stimulation inhibited caspase-3 activation and reduced apoptotic neuronal death in DRG explants. It was suggested that the neuroprotective effect of electrical stimulation is likely mediated by the inhibition of caspase-3 activation and therefore the inhibition of apoptosis following ara-C treatment.
Keywords: CENTRAL-NERVOUS-SYSTEM; MULTIELECTRODE ARRAYS; SYMPATHETIC NEURONS; IN-VITRO; CHEMOTHERAPY; EXPRESSION; LEUKEMIA; GROWTH; BDNF; NGF